(untitled) (Research, Society and Development, 2023)
The objective was to understand the effectiveness of the pharmacist’s role in preventing and reducing the number of cases of drug poisoning in the elderly attributed to self-medication. Following the recommendations adapted from the PRISMA guideline, a search was carried out in the PubMed and MEDLINE databases, considering as eligibility criteria the availability of the full text, language and year of publication, only studies published in Portuguese or English, between January 2013 and September 2023. We demonstrate that the pharmacist is essential to reduce the use of potentially inappropriate medications prescribed to the elderly, warn about possible adverse effects, identify elderly people at risk for self-medication and manage polypharmacy in the best possible way. The ease of access to such professionals makes them essential for the health education process, guidance on self-care, control of self-medication, instructions on the correct use of prescribed medications and early identification of adverse effects to avoid masking serious illnesses. Although well established, the role of the pharmacist in reducing the number of cases of poisoning due to self-medication in the elderly is still not exercised as frequently as expected. New research should identify the main barriers for pharmacists to act in preventing irresponsible self-medication in the elderly, determine strategies for identifying elderly people at higher risk and intervention protocols. Only in this way will pharmaceutical intervention be standardized and can be put into practice to reduce cases of self-medication poisoning in the elderly.